Enabling use of cybernetic control systems in a knowledge-intensive organization - Ståhlberg, Eero (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2018)
The main purpose of this doctoral thesis is to enhance our understanding, through an in-depth case study, on how to reach enabling formalization with the help of which control systems and related processes could concurrently facilitate efficiency and innovation. In the current knowledge economy, how to better manage such tensions is a key issue in many organizations. To solve this ambidextrous dilemma of formalization, Adler and Borys (1996) introduced the theoretical notion of enabling bureaucracy with four specific characteristics, namely internal transparency, global transparency, repair, and flexibility. Despite the existence of the four enabling features in the case organization’s cybernetic control systems (see Malmi & Brown 2008, 291; Green & Welsh 1988, 289), counterevidence regarding the postulated associations between the four specific characteristics of Adler & Borys (1996) and innovation, and especially its critical component of motivation was obtained. Notions from the psychological self-determination theory (e.g. Deci & Ryan 1985) were thereby brought into the analysis. The theory contends that for autonomous forms of motivation to arise, individual’s three basic needs – competence, autonomy, and relatedness – must be fulfilled (Deci & Ryan 1985). By using abduction in interpreting the acquired case study evidence, I came to appreciate many of the findings of Adler and Borys (1996) as well as Adler and Chen (2011) as the four enabling features supported innovation and autonomous motivation in several ways. While the findings support their view about the encouragement of motivation through internalization of both goals and of the discipline necessary to reach them, they concurrently indicate that the four features may not always be sufficient to support such processes. The basic psychological need of relatedness is in prior literature argued to be highly important for such processes of internalization and, to support it, cybernetic control system systems with relative evaluation processes and pressures can play an important part. I suggest that in the knowledge-intensive case organization, the failure in the internalization of values was associated with relatedness – due to an absence of right kind of pressure through the cybernetic control systems. The organizational members were in a relatively passive way engaged in using prior knowledge rather than enthusiastically creating new knowledge, although the latter was realised to be critical for the company’s future success. It is thereby argued that for managers to adequately support their subordinates’ motivational orientations and subsequent activities of innovation, introducing a right amount of pressure may be critical. However, managers should simultaneously acknowledge the delicate balance of such processes.

Tämän tutkimuksen tavoitteena on edistää syvälliseen tapaustutkimukseen nojaten ymmärrystämme siitä, miten johdon ohjausjärjestelmät ja niihin liittyvät prosessit voisivat samanaikaisesti tukea operatiivista tehokkuutta ja innovointia. Monessa organisaatiossa näiden usein ristiriitaisten pyrkimysten johtaminen on tärkeä haaste nykyisessä tietointensiivisessä yritysympäristössä. Adler ja Borys (1996) ovat esitelleet niiden välisten jännitteiden tasapainoittamiseksi viitekehyksen, joka sisältää neljä ohjausjärjestelmien erityispiirrettä: ‘järjestelmän läpinäkyvyys’, ‘operatiivinen läpinäkyvyys’, ‘prosessin kehitysmahdollisuus’ ja ‘joustavuus’. Vaikka Adlerin ja Borysin (1996) teoreettisen viitekehyksen neljä erityispiirrettä olivat suurelta osin havaittavissa kohdeorganisaation kyberneettisissä ohjausjärjestelmissä (kts. Malmi & Brown 2008, 291; Green & Welsh 1988, 289), löydökset viittaavat siihen, että innovointia ja erityisesti sen tärkeää komponenttia (autonomista) motivaatiota ei näiden järjestelmien kautta tuettu organisaatiossa riittävästi. Motivaatioon liittyvät havainnot viitoittivat analysoimaan tutkimuksen löydöksiä psykologian kirjallisuuden avulla ja soveltamaan itseohjautuvuusteoriaa (esim. Deci & Ryan 1985), joka korostaa autonomisen motivaation saavuttamisessa kolmen perustarpeen (‘kyvykkyys’, ‘omaehtoisuus’ ja ‘yhteisöllisyys’) tyydyttämistä (Deci & Ryan 1985). Tapaustutkimuksessa hyödynnettyä abduktiivista päättelyä seuraamalla todettiin, että Adlerin ja Borysin (1996) neljä erityispiirrettä tukevat tutkittavan organisaation innovointia ja sen keskeistä motivaatio-komponenttia usealla eri tavalla. Tutkimuksen materiaali osoittaa kuitenkin myös, että neljä viitekehyksen erityispiirrettä eivät välttämättä tue riittävästi organisaation arvojen ja tavoitteiden sisäistämistä ja siten motivaatiota (vrt. Adler & Borys 1996; Adler & Chen 2011). Tavoitteiden sisästämisessä ‘yhteisöllisyyden’ tarpeen tyydyttyminen on kriittistä ja tätä voivat kyberneettiset ohjausjärjestelmät oikeanlaisen ohjauspaineen kautta tukea. Tutkimuksen löydökset kuitenkin viittaavat siihen, että ’yhteisöllisyyden’ tarvetta ei kohdeorganisaatiossa riittävästi tuettu näiden järjestelmien kautta oikeanlaisen ohjauspaineen puutteesta johtuen. Tietointensiivisessä kohdeorganisaatiossa tämä ilmeni siten, että sen jäsenet keskittyivät enemmän olemassa olevan tiedon käyttöön kuin kehittivät innokkaasti uutta, vaikka juuri innovointitoimintojen tiedostettiin olevan yritykselle kriittisiä menestystekijöitä. Tältä pohjalta tutkimuksessa ehdotetaan, että tukeakseen alaistensa motivaatiota ja siihen pohjautuvia innovaatioprosesseja, johtajien tulee sopivassa määrin antaa oikeanlaista ohjauspainetta ja yhteisöllistä tukea alaisilleen. Heidän tulee samalla kuitenkin ottaa huomioon tällaisten prosessien herkkä tasapaino.